2016
DOI: 10.1021/jacs.6b10169
|View full text |Cite
|
Sign up to set email alerts
|

Reversible Transformation of Pt Nanoparticles into Single Atoms inside High-Silica Chabazite Zeolite

Abstract: We report the encapsulation of platinum species in highly siliceous chabazite (CHA) crystallized in the presence of N,N,N-trimethyl-1-adamantammonium and a thiol-stabilized Pt complex. When compared to Pt/SiO or Pt-containing Al-rich zeolites, the materials in this work show enhanced stability toward metal sintering in a variety of industrial conditions, including H, O, and HO. Remarkably, temperatures in the range 650-750 °C can be reached without significant sintering of the noble metal. Detailed structural … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

20
412
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 391 publications
(435 citation statements)
references
References 41 publications
20
412
0
3
Order By: Relevance
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] Small-pore zeolites also exhibit enhanced hydrothermal stability in comparison to their medium-and large-pore analogues. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] Small-pore zeolites also exhibit enhanced hydrothermal stability in comparison to their medium-and large-pore analogues.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] Small-pore zeolites also exhibit enhanced hydrothermal stability in comparison to their medium-and large-pore analogues. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] Small-pore zeolites also exhibit enhanced hydrothermal stability in comparison to their medium-and large-pore analogues.…”
mentioning
confidence: 99%
“…[22,23] Theintroduction of transition-metal cations of large ionic radii into small pore zeolites using traditional post-synthetic preparation methods (e.g., ion exchange) has proven difficult. [16,[26][27][28][29][30][31][32][33][34] Molliner et al demonstrated ar oute to produce 0.23 wt %a tomically dispersed Pt in SSZ-13 with Si/Al ratio 7t o9 . [24,25] Today,t here is ag reat interest to produce small-pore zeolites loaded with atomically dispersed Pt and Pd at levels higher than 0.3 wt %.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…During the synthesis process, the polydopamine‐coated a‐FeOOH nanorod was carbonized, and then leached by HCl, resulting in the isolated Fe atoms on the inner surface of N‐doped carbon ( Figure a) . In addition, by thermal calcination at high temperature in oxidative atmosphere, isolated metal atoms could be derived from bulk metal . For example, Moliner et al found the metal nanoparticles, such as Pt and Pd, can be fragmented into smaller particles or even subnanometric species via calcination treatment in oxidative atmosphere (Figure b) .…”
Section: Synthesis Strategies For Single Metal Atom Catalystsmentioning
confidence: 99%